Myocardial Ischemia and Mobilization of Circulating Progenitor Cells. Issue 4 (10th February 2018) - Hammadah, Muhammad; Samman Tahhan, Ayman; Mheid, Ibhar Al; Wilmot, Kobina; Ramadan, Ronnie; Kindya, Bryan R.; Kelli, Heval M.; O'Neal, Wesley T.; Sandesara, Pratik; Sullivan, Samaah; Almuwaqqat, Zakaria; Obideen, Malik; et al.
Abstract : Background: The response of progenitor cells (PCs) to transient myocardial ischemia in patients with coronary artery disease remains unknown. We aimed to investigate the PC response to exercise‐induced myocardial ischemia (ExMI) and compare it to flow mismatch during pharmacological stress testing. Methods and Results: A total of 356 patients with stable coronary artery disease underwent 99mTc‐sestamibi myocardial perfusion imaging during exercise (69%) or pharmacological stress (31%). CD34 + and CD34 + /chemokine (C‐X‐C motif) receptor 4 PCs were enumerated by flow cytometry. Change in PC count was compared between patients with and without myocardial ischemia using linear regression models. Vascular endothelial growth factor and stromal‐derived factor‐1α were quantified. Mean age was 63±9 years; 76% were men. The incidence of ExMI was 31% and 41% during exercise and pharmacological stress testing, respectively. Patients with ExMI had a significant decrease in CD34 + /chemokine (C‐X‐C motif) receptor 4 (−18%, P =0.01) after stress that was inversely correlated with the magnitude of ischemia ( r =−0.19, P =0.003). In contrast, patients without ExMI had an increase in CD34 + /chemokine (C‐X‐C motif) receptor 4 (14.7%, P =0.02), and those undergoing pharmacological stress had no change. Plasma vascular endothelial growth factor levels increased (15%, P <0.001) in all patients undergoing exercise stress testing regardless of ischemia. However, the change in stromal‐derived factor‐1α level correlated inversely with the change in PC counts in those with ExMI ( P =0.03), suggesting a greater decrease in PCs in those with a greater change in stromal‐derived factor‐1α level with exercise. Conclusions: ExMI is associated with a significant decrease in circulating levels of CD34 + /chemokine (C‐X‐C motif) receptor 4 PCs, likely attributable, at least in part, to stromal‐derived factor‐1α–mediated homing of PCs to the ischemic myocardium. The physiologic consequences of this uptake of PCs and their therapeutic implications need further investigation.